1973
DOI: 10.1182/blood.v41.1.59.59
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Pattern of Neutrophil Kinetics in Sickle Cell Anemia

Abstract: Blood neutrophil kinetics were studied withwith DF32P in patients with sickle cell anemia. Neutrophil concentration in venous blood samples and the size of the circulating granulocyte pool (CGP) were high normal or abnormally high in all patients. The total blood granulocyte pool (TBGP) was not increased to the same degree as the CGP so that in part, the neutrophilia associated with sickle cell anemia represents a shift from marginated to circulating blood compartments. The half disappearance time (T½) of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…The concentration of PMNs in pulmonary capillary blood is 40-80 times higher than seen in the blood of large vessels (5,15). Many individuals with SCD have chronically elevated peripheral white blood cell counts in the absence of an acute crisis, which suggest the marginal pool of PMNs in the pulmonary circulation may be higher than that reported in normals (8,14). Boghossian et al (9) and Fadlon et al (18) have demonstrated that PMNs from patients in crisis are more adherent than control PMNs and suggest that enhanced PMN adhesion to vascular endothelium could contribute to the initiation of vasoocclusion in the acute crisis of SCD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of PMNs in pulmonary capillary blood is 40-80 times higher than seen in the blood of large vessels (5,15). Many individuals with SCD have chronically elevated peripheral white blood cell counts in the absence of an acute crisis, which suggest the marginal pool of PMNs in the pulmonary circulation may be higher than that reported in normals (8,14). Boghossian et al (9) and Fadlon et al (18) have demonstrated that PMNs from patients in crisis are more adherent than control PMNs and suggest that enhanced PMN adhesion to vascular endothelium could contribute to the initiation of vasoocclusion in the acute crisis of SCD.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators (9,18) have demonstrated that PMNs from some patients in crisis are more adherent to vascular endothelium than during steady state and possibly contribute to vasoocclusion. Clinical studies show that elevated total white blood cell counts are common in SCD (8,14) and that a white blood cell count Ͼ15,000 cells/ml is associated with an increased risk of early death (51). Cytokines such as interleukin-6 have been correlated positively with the number of sickle PMNs adherent to fibronectin (36).…”
mentioning
confidence: 99%
“…Sickle disease is an inflammatory state, as evidenced in humans by chronic elevation of leukocyte counts (169), shortened leukocyte half-life (19), and abnormal activation of granulocytes and monocytes (15,17,45,83,86,113,197). The phenotype of circulating endothelial cells in sickle blood is abnormally activated and proadhesive (positive for VCAM, ICAM, selectins, α v β 3 ), procoagulant (positive for tissue factor), and oxidatively stressed (upregulated heme-oxygenase-1) (129,163,164).…”
Section: Inflammationmentioning
confidence: 99%
“…White blood cell (WBC) or leukocyte count is a blood test used to detect a range of blood disorders, evaluate the severity of various underlying diseases, and at times predict the risk of death. 1 7 Several previous reports revealed a possible association between WBCs and severity of sickle cell disease (SCD). 7 10 Buchanan and Glader 11 reported that WBC counts were significantly increased during serious bacterial infection and vaso-occlusive crisis among children with SCD.…”
Section: Introductionmentioning
confidence: 99%